QR codes: A case of its level of adoption in Portugal - Lopes Bolzan, Roberson (2022)
The choice of this work arises from the interest in the topics of entrepreneurship and technology transfer toward launching more innovative products/services. It focuses on delivering a technology, QR code, which brings more innovation to a product especially with the current growth of mobile activities. Then, with the help of a strategic plan, it evaluates the level of potential acceptation and adoption of the proposed service and of widespread use of QRs in Portugal. Thus, an interactive prototype of the supporting platform is described and used for its validation with users. Most participants in this project know the technology and consider the idea interesting and promising. They even suggest add-ons such as more video functions and a higher variety of events and/or resources for combination. However, through a deeper analysis, aspects related with effective use of the service, eventual payment, and explaining how it works reveal lower enthusiasm. Thus, although there is a promising scenario for its implementation in the Portuguese market, training aimed at effectively knowing and using QR-code technology must evolve. Given the challenges of today's society, the future application of this product/service shall pass through an innovation acspecialized information or resources for activities in the areas of tourism, banking, health, etc.